2020
DOI: 10.1158/0008-5472.can-19-0656
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bioengineered miR-127 Prodrug Suppresses the Growth and Metastatic Potential of Triple-Negative Breast Cancer Cells

Abstract: ◥ miR-127 is downregulated in breast cancer, where it has been shown to suppress the proliferation, migration, and invasion of breast cancer cells. In triple-negative breast cancer (TNBC), miR-127 downregulation correlates with decreased disease-free and overall patient survival. Tumor suppressor miRNAs may hold therapeutic promise but progress has been limited by several factors, including the lability and high cost of miRNA mimics. Here, we take a novel approach to produce a miR-127 prodrug (miR-127 PD ), wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 60 publications
(75 reference statements)
0
26
0
Order By: Relevance
“…The diagnostic and prognostic potential of miRNAs for tumors has recently been reported, with a number of miRNAs being used a tumor biomarkers and targeted drugs ( 31 ). Moreover, miRNAs are involved in osteosarcoma-associated signaling pathway regulation, which provides a novel strategy for identifying the molecular mechanisms underlying osteosarcoma ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic and prognostic potential of miRNAs for tumors has recently been reported, with a number of miRNAs being used a tumor biomarkers and targeted drugs ( 31 ). Moreover, miRNAs are involved in osteosarcoma-associated signaling pathway regulation, which provides a novel strategy for identifying the molecular mechanisms underlying osteosarcoma ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…uni-heidelberg.de/). Among these target genes of miR-25-5p, KLK9, WNT3A, FGF18, SRSF4, FIBP, SOX12, TGFBI, and NEDD9 have been reported to participate in the development human cancers (42)(43)(44)(45)(46)(47)(48)(49). Thus, we selected these genes for further investigation.…”
Section: Mir-25-5p Regulates Oscc Cell Proliferation Invasion and Mmentioning
confidence: 99%
“…They lead to the silencing of respective gene expression either by direct degradation of mRNA or inhibition of protein translation [ 11 , 12 ]; miRNAs are involved in a wide range of cancer biology processes, including regulation of target mRNA expression, which promotes tumor growth, apoptosis, progression, metastasis, and immune evasion [ 13 , 14 , 15 , 16 ]. Many studies have reported that miRNAs play key roles in the occurrence and progression of breast cancer [ 17 , 18 , 19 , 20 ]; this has prompted translational studies on miRNAs for breast cancer to be actively conducted [ 21 ].…”
Section: Introductionmentioning
confidence: 99%